The profile of the municipal public manager in Huánuco city – 2018 - Abal-García, Hamilton D. (2020)
The objective of this research was to describe the profile of the municipal public manager in the city of Huánuco, in 2018. Methods: The focus of the study was quantitative, with a descriptive, non-experimental, cross-sectional and prospective design. A non-probabilistic sampling method was applied for the convenience of the researcher, made up of 60 municipal managers from the city of Huánuco, representing 100% of the population. In data collection, an interview with general characteristics and a questionnaire on the profile of the municipal manager were applied, previously validated and reliable. Ethical considerations for research were applied. The data were analyzed applying descriptive statistics. The results show that 63.3% (38) of the municipal managers in the study showed conceptual skills of an intermediate level, related to the public budget and management for results; followed by 50% (30) who mastered advanced level human skills, with entrepreneurial vision predominant in 48.3% (29), followed by teamwork in 47.3% (28). Also, 43.3% (26) achieved an intermediate level in these skills with respect to the vocation of service. Regarding technical skills, 50.0% (30) (30) showed an advanced level, with respect to mastery of Microsoft Office and Software in their work area, followed by 48.3% (29) who dominated digital communication over the Internet and 33.3% (20) the intranet. It is concluded that technical skills prevailed at the advanced level in 50% (30), followed by 33.4% (20) in human skills. And 43.3% (26) showed conceptual skills at an intermediate level.